Residual mitral regurgitation impact on outcomes after mitraclip therapy: five-year follow-up from the GRASP registry. (8th February 2021) - Caggegi, AM; Capranzano, P; Scandura, S; Mangiafico, S; Castania, G; Salerno, T; Milici, A; De Sanctis, J; Bentivegna, A; Frazzetto, M; Sardone, A; Di Salvo, ME; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background – Although percutaneous mitral valve repair is an attractive alternative treatment option for patients with severe mitral regurgitation (MR) at high surgical risk, residual MR is commonly observed after the procedure and little is known about its impact on outcomes after MitraClip therapy, expecially in patients with severe left ventricular (LV) impairment. Purpose – The aim of this prospective, observational study was to evaluate the impact of residual MR (MR ≤1+ vs. MR >1+) on long-term outcomes of mitral valve repair with the MitraClip System in high surgical risk patients presenting with moderate-to-severe or severe MR and with severe reduction of LV ejection fraction (EF). Methods – Patients enrolled in the prospective Getting Reduction of Mitral Insufficiency by Percutaneous Clip Implantation (GRASP) with functional MR and EF ≤30% who were eligible at almost five-year follow-up were included in the present analysis.  The primary endpoint was death at 5-year follow-up.  Also echocardiographic parameters at baseline and 5-year follow-up and rehospitalization rates were assessed. Results – A total of 139 patients were included: 92 (66.2%) with post-procedural residual MR ≤1+ and 47 (33.8%) with residual MR > 1+ (41 patients with residual MR 2+, 5 with residual MR 3+, 1 with residual MR 4+).  Comparable clinical and echocardiographic baseline characteristics were observed between the two groups except for NYHA functional class IV and implanted pace-maker (more frequent in patients with residual MR >1+) and previous myocardial infarction (more frequent  in patients with residual MR ≤1+). At 5-year follow-up, no significant differences were reported in the primary endpoint (49.6% in patients with residual MR ≤ 1+ vs. 65.3% in patients with residual MR > 1+, p 0.203) and in cardiac death (37.8% in patients with residual MR ≤ 1+ vs. 42.6% in patients with residual MR > 1+, p 0.921). Cox regression analysis identified residual MR > 1+ as an independent predictor of re-hospitalization (HR 0.51, 95% CI 0.28-0.92, p =0.026). At 5-year follow-up,   a significant reduction in left ventricular end-systolic volume was  observed in patients with residual MR ≤ 1+. Conclusions – At 5-year follow no significant differences in survival emerged in patients with severe  LV dysfunction undergoing MitraClip therapy regardless residual MR. Nevertheless residual MR > 1+ emerged as an indipendent predictor of re-hospitalization.